Eksplorasi Pembelajaran Hybrid di Universitas Muhammadiyah Gresik dari Perspektif Mahasiswa (Studi Kasus: Jurusan Teknik Informatika) - Muhammad Wildan Cahya Purnama; Diah Priharsari; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
COVID-19 spreads rapidly which affects various sectors and one of them is the education sector, previously people came to campus for offline learning but nowadays it becomes online learning. The Ministry of Education and Culture stated as in the announcement to implement a hybrid learning policy. One of the universities that implement this hybrid learning is Muhammadiyah Gresik University. The research is done by using a qualitative research method to understand the process of hybrid learning and the problems encountered during the hybrid learning from the exploration that has done. The exploration is done by using semi-structured interview data collection techniques. The results of interviews with nine interviewees then transcribed and analyzed with thematic analysis to get the suitable themes and categories. From the research analysis results, the students were found not familiar enough with this hybrid learning because it was online learning before, so needed to do hybrid learning exploration to knowing how hybrid is implemented, what problems they faced, and what solution that they doing. There are many problems faced by the students in carrying out the hybrid learning for the first time, like being late for attendance because there was no notification and feel bored while attending lectures so that make sleepy. There was some solution to deal with it, such as asking friends and lecturers for help to solving the problems.